Analisis Kebutuhan Bahan Ajar Matematika Berpendekatan Problem Based Learning (PBL) - Ningrum, Izza Eka (TSAQOFAH, 2023)
Teaching facilities used by students so far have not provided initiative in the learning process. This study aims to analyze the need for teaching materials according to the problem based learning (PPL) method. This research is a qualitative research with descriptive qualitative research type. The research subjects were class VII junior high school students. Research data was collected through interviews and observation. The results of the study show that: (1) All curriculum contents are in accordance with KI, KD (2) Teachers and students do not understand the contents of the curriculum (3) Teachers and students are interested in teaching materials in the PBL Approach (4) Teachers and students need to learn with the PBL PBLroach because it makes students actively participate in the learning process in class. Therefore, teaching materials with a PBL PBLroach are needed.